New species of Creagrutus Günther (Characiformes: Characidae) from rio Tapajós basin, Brazil, with comments on its phylogenetic position - Dagosta, Fernando Cesar Paiva; Pastana, Murilo Nogueira De Lima (Zootaxa, 2014)
Creagrutus nigrotaeniatus n. sp. is described from the rio Juruena basin, upper rio Tapajós system, Mato Grosso State, Brazil. Creagrutus nigrotaeniatus differs from its congeners by having the dentigerous surface of the premaxilla longitudinally elongate from ventral view, 4–5 post-anal scales and 2–4 maxillary teeth. The new species also has the anterior margin of hyomandibula straight or slightly concave which is a unique condition within the genus, and possesses a series of non-exclusive osteological modifications (e.g. medial opening of the dentary foramen located distinctly anteroventral to the tip of Meckel’s cartilage; anterior portion of the laterosensory canal segment in first infraorbital terminating distinctly posterior to the anterior margin of this bone; presence of the third posttemporal fossa within the epioccipital; one epural present). A comparison with Caiapobrycon tucurui is provided and the placement of the new species within Creagrutus and its close relationship with C. cracentis, C. gephyrus, and C. maxillaris are discussed.